Phosphorus availability in casts of an anecic savanna earthworms in Colombian oxisol - Jiménez Jaén, J.J.; Cepeda, A; Friesen, Dennis K.; Decaëns, Thibaud; Oberson, Astrid (International Center for Tropical Agriculture, 2001)
Earthworms are considered soil ecosystem engineers that play an important role in soil organic matter dynamics and physical structure. Due to both their size and activities these organisms can accelerate the decomposition and mineralization of organic matter by reducing the size of residues to particles more available to microflora. Consequently, their impact in nutrient availability and cycling in natural and agricultural ecosystems can be considerable. Three experiments were performed in a natural herbaceous savanna and in a selected Brachiaria decumbens and Pueraria phaseoloides ("Kudzu") pasture: one field study and two laboratory/incubation studies, at the CIAT-CORPOICA research station at Carimagua in the isohyperthermic savannas on the Colombian Orinoco basin. Total P content was higher in earthworm casts than in the surrounding soil in field samples, i.e., 50% in native savanna soil and more than 100% in pasture soil, but not (or very little) in laboratory casts (10%-20%). Under field conditions almost without exception, all P fractions increased in casts compared with the control soil. Increases were relatively greater in the labile inorganic P fractions. Except in the native savanna under field conditions, the phosphatase activity was reduced on casting. Our results suggest that earthworms in the field incorporate P from litter or undecomposed plant and root material which is not normally measured in the analysis of bulk (non-cast) soil. This P from litter enters into all P fractions (organic and inorganic) but to a greater extent into labile Pi fractions. The objective of this study was to assess the effect of an abundant native anecic earthworm on phosphorus availability in Oxisols of supposedly low fertility characteristics.